Social policy of the Scandinavian countries in relation to women victims of domestic violence - R. M. Sadykov; N. L. Bolshakova (Вестник университета)
The article examines the issue of domestic violence against women as a widespread global social problem of modern society. Many countries are taking various measures to prevent and mitigate this problem. The scientific work presents the experience of solving such a problem in the Scandinavian countries, where an effective model of social policy is implemented in relation to women victims of marital violence. It is highlighted that the importance and relevance of this problem has increased in recent years during the global Covid-19 pandemic, when universal social isolation was introduced. The purpose of the scientific article is to study the state of the social policy of the Scandinavian countries in relation to marital violence against women. The main directions of the family policy of the Scandinavian countries are defined, which is based on the formation of a safe environment for creating a family and raising children. Within the framework of this study, the main programs for the prevention of family violence and the treatment of its victims, social services provided and support systems by social, psychological and medical services are presented. It was also revealed that the support programs are mainly aimed at protecting and establishing the security boundary, restoring the self-esteem of victims of domestic violence.